URGENSI PEMAHAMAN MAKNA SIMBOL BUDAYA JAWA DI PASAR KERAMAT PACET MOJOKERTO: KAJIAN SEMIOTIK - Hidayat Ali Haromaini; Khusnul Khotimah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This research is motivated by Javanese culture which has an important role for the nation today in facing foreign cultural competition that prioritizes modern or hedonistic life. This preservation is important to do so that Javanese culture is not sidelined by the modern era. Therefore, the establishment of the Keramat market which stores Javanese cultural symbols is important to be developed in order to face modern competition. So, this study aims to reveal the meaning of the symbols of snacks, drinks, and performing arts that reflect Javanese culture in the Keramat market. This study uses a research method in the form of a qualitative approach and a descriptive method is used to interpret or describe the signifiers and markers of Javanese cultural symbols in the Keramat Market. Based on the use of a qualitative approach and descriptive method, it will produce results that show that there is a denotative, connotative, and mythical meaning of Roland Barthes' semiotic theory concept in snacks, drinks, and performing arts that reflect Javanese culture in the Keramat market. So the concept of Barthes' semiotic theory in the form of denotative meaning through signifiers and markers aims to reveal the literal meaning of the data to be used. The connotative meaning is useful for knowing the signifiers and signifieds of the symbols of snacks, drinks, and performing arts that reflect Javanese culture in the Keramat market. Furthermore, the myth which is derived from the signified connotative meaning is useful for expressing the deep meaning of the symbols of Javanese culture in the Keramat market.